A Bistatic ISAC Framework for LEO Satellite Systems: A Rate-Splitting Approach - Park, Juha; Seong, Jaehyup; Mao, Yijie; Shin, Wonjae; Ottersten, Bjorn (IEEE transactions on aerospace and electronic systems, 2025)
Achieving ubiquitous connectivity and radar sensing on the same platform with improved spectral/energy efficiency is a critical challenge for low Earth orbit (LEO) satellite systems. To mitigate severe radar echo loss at high altitudes, we put forth a bistatic integrated sensing and communication (ISAC) framework, where a ground-based radar receiver operates separately from the satellite. For robust and effective interference management, we employ rate-splitting multiple access (RSMA), which splits and encodes users' messages into private and common streams. Instead of relying on instantaneous communication channel state information (CSI), we exploit the geometric and statistical characteristics of the satellite channel while accounting for uncertainty in the geometric information. Based on this practical modeling, we optimize the robust dual-functional precoders to maximize the minimum user rate while satisfying Cramér-Rao bound (CRB) constraints. To achieve this, we develop an efficient optimization algorithm using multiple mathematical relaxation techniques for joint precoder design. Numerical results show that the proposed framework efficiently performs both communication and radar sensing, exhibiting strong interference mitigation even under geometric channel uncertainty. Furthermore, it is validated that the common stream plays three vital roles: i) beamforming towards the radar target, ii) interference management between communications and radar, and iii) interference management among communication users. By leveraging the multi-functionality of the common stream, efficient and robust joint operation of radar sensing and communication is achieved even without requiring a dedicated radar sequence.